DETEKSI DISTRIBUSI WHITE SPOT SYNDROME VIRUS PADA BERBAGAI ORGAN UDANG VANAME (Litopenaeus vannamei) - Hidayani, A.Aliah; Malina, Asmi C.; Tampangallo, Bunga R.; Fathurrahman, Achmad F. (Hasanuddin University, 2015)
One way to detect the presence of the White Spot Syndrome Virus in several organs Vaname shrimp(Litopenaeus vannamei) were infected with the method of Polymerase Chain Reaction (PCR). WSSV virus isknown to attack various target organs, but it is difficult to detect early on shrimp. Therefore, this study aims todetect the presence of the distribution of White Spot Syndrome Virus in several organs Vaname shrimp(Litopenaeus vannamei) were infected with the Polymerase Chain Reaction method in order to early detectionefforts for the prevention and treatment of diseases caused by the virus. Organ observed that the swimming legs,gills, stomach and antennal gland. Research stages include sample preparation and DNA extraction, DNAamplification and electrophoresis. DNA extraction was performed using the method DTAB and CTAB-DNAamplification is done by using nested PCR. The emergence of DNA bands is an indicator of the presence ofWSSV in shrimp Vaname several organs which are then presented desktriptif. The results showed four WSSVinfected organs were observed. Based on the appearance, the entire sample of the swimming leg and antennalgland positively infected, then successively gills and stomach. The swimming leg can be used to diagnose thedisease early on shrimp WSSV Vaname without turning off the shrimp.Keywords : Distribution, Vanname shrimp, WSSV, PCR